2007
DOI: 10.1590/s0100-879x2007000400012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnosis of malaria by microscopy, immunochromatography and PCR in endemic areas of Venezuela

Abstract: Whole blood samples (N = 295) were obtained from different locations in Amazonas and Sucre States, in Venezuela. Malaria was diagnosed by microscopy, OptiMAL™ and polymerase chain reaction (PCR), with Plasmodium vivax, P. falciparum, and P. malariae being detected when possible. We identified 93 infections, 66 of which were caused by P. vivax, 26 by P. falciparum, and 1 was a mixed infection. No infection caused by P. malariae was detected. The sensitivity and specificity of each diagnostic method were high: 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 32 publications
4
25
0
2
Order By: Relevance
“…Palmer et al (2003 did not stratify their study population and used the more relevant Polymerase Chain Reaction (PCR) to validate the DiaMed OptiMAL-IT results. Similar results and observations for sensitivity (87.0%) and specificity (97.9%) of DiaMed OptiMAL-IT have been recorded in Venezuela by Rodulfo et al (2007). In the present study, although PCR was not performed, we find the DiaMed OptiMAL-IT antigen assay to have relatively low performance indices, especially for malaria infections with low parasite densities.…”
Section: Discussionsupporting
confidence: 90%
“…Palmer et al (2003 did not stratify their study population and used the more relevant Polymerase Chain Reaction (PCR) to validate the DiaMed OptiMAL-IT results. Similar results and observations for sensitivity (87.0%) and specificity (97.9%) of DiaMed OptiMAL-IT have been recorded in Venezuela by Rodulfo et al (2007). In the present study, although PCR was not performed, we find the DiaMed OptiMAL-IT antigen assay to have relatively low performance indices, especially for malaria infections with low parasite densities.…”
Section: Discussionsupporting
confidence: 90%
“…3 Several studies in various parts of the world have revealed the high prevalence of mixed-species infections using PCR. 9,10 Even in very low parasitemia, P. vivax and P. falciparum have been detected using this method.…”
Section: Introductionmentioning
confidence: 95%
“…We have determined the sensitivity/specificity of the PCR method in the same malaria areas in a previous study (Rodulfo et al 2007a). …”
Section: Subjects Materials and Methodsmentioning
confidence: 99%